2009
DOI: 10.4081/1208
|View full text |Cite
|
Sign up to set email alerts
|

Adult mesenchymal stem cells for bone and cartilage engineering: effect of scaffold materials

Abstract: Bone marrow is a useful cell source for skeletal tissue engineering approaches. In vitro differentiation of marrow mesenchymal stem cells (MSCs) to chondrocytes or osteoblasts can be induced by the addition of specific growth factors to the medium. The present study evaluated the behaviour of human MSCs cultured on various scaffolds to determine whether their differentiation can be induced by cell-matrix interactions. MSCs from bone marrow collected from the acetabulum during hip arthroplasty procedures were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…In this technique microfractures should permit the migration of mesenchimal stem cells (MSCs) from the subchondral bone, and the scaffold should keep cells in situ and serve as support for tissue differentiation. In vitro studies have already demonstrated that human MSCs grown on collagen scaffolds may proliferate and differentiate into chondrocytes without growth factor supplementation (8). However, the presence of MSCs in subchondral bone of the femur or tibia in adults is small in comparison with their presence in a bone marrow aspirate form the iliac crest (9).…”
mentioning
confidence: 99%
“…In this technique microfractures should permit the migration of mesenchimal stem cells (MSCs) from the subchondral bone, and the scaffold should keep cells in situ and serve as support for tissue differentiation. In vitro studies have already demonstrated that human MSCs grown on collagen scaffolds may proliferate and differentiate into chondrocytes without growth factor supplementation (8). However, the presence of MSCs in subchondral bone of the femur or tibia in adults is small in comparison with their presence in a bone marrow aspirate form the iliac crest (9).…”
mentioning
confidence: 99%
“…In this context, the bioengineering challenge become ambitious, since the complex cellbiomaterial interaction moves on multiple spatial and temporal scales. The microenvironmental cues, such as chemical environmental variables, are able to stimulate specific cellular responses at the molecular level already at early time points (Goshima, Goldberg et al 1991;Ohgushi, Dohi et al 1993;Fabbri, Celotti et al 1995;Kon, Muraglia et al 2000;Erbe, Marx et al 2001;Endres, Hutmacher et al 2003;Kasten, Luginbuhl et al 2003;Livingston, Gordon et al 2003;Niemeyer, Krause et al 2003;Arinzeh, Tran et al 2005;Kotobuki, Ioku et al 2005;Kondo, Ogose et al 2006;Fan, Ikoma et al 2007;Mygind, Stiehler et al 2007;Gigante, Manzotti et al 2008;Ng, Tan et al 2008;Bernhardt, Lode et al 2009;Saldana, Sanchez-Salcedo et al 2009). For example, ceramic scaffolds (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…enamel matrix derivative and growth factors, 3,4 and local delivery of growth factors via gene therapy 5,6 prevents the progression of periodontal disease and promote regeneration. In recent years, different types of stem cells, including bone marrow stem cells (BMSCs), 7,8 periodontal ligament progenitor cells (PDLSCs), [9][10][11] adipose-derived stem cells 12,13 and mesenchymal stem cells [14][15][16] have been investigated for periodontal regeneration. Among these, both PDLSCs and BMSCs are multipotent, have no risk of immune rejection, are noncarcinogenic and are currently in clinical trials.…”
Section: Introductionmentioning
confidence: 99%